Analisis Pengaruh Basic Earning Power, Struktur Modal, Dan Kebijakan Dividen Terhadap Harga Saham Perusahaan - Muktiadji, Nusa; Ningrum, Eka Soesilawati (Jurnal Ilmiah Manajemen Kesatuan, 2018)
Stock price movement is a reflection of a company value caused by many factors, both of internal and external. The higher stock price means higher the company value and it will better attract the investors. Variables used in this research consist of three independent variables, they are Basic Earning Power with Basic Earning Power as the indicator, Capital Sturcture with Debt to Equity Ratio (DER) as the indicator, and Dividend Policy with Dividend Payout Ratio (DPR) as the indicator, and one dependent variable that is Stock Price. Research period is during year 2005 until 2014. Data that used in this research is quantitative data with secondary source which analysed by trend method, regression, significance F and t test, and coefficient of determination. Trend analysis is used to determine the trend of the movement of all variables during the period of year 2005 until 2014. Regression analysis is used to determine direction and influenceof the independent variables to the dependent variable. Sigificance test is used to determine whether influence of the independent variable to the dependent is significantly to α 5% (0.05). The Correlation analysis and determination is used to know level of the correlation and strength of the independent variables to the dependent variable.The trend analysis method showed that during the research period basic earning power, capital structure, and dividend policy is increase and decrease. Classic assumption test showed that all of data that used in the research was completed the requirement. The result of the research showed that partially, capital structure variable had a real influence to the company stock price. As we could see that F test point for capital structure is 4,690 andsignificance point is 0,000. Then the rest of the variables, there are basic earning power and dividend policy didn’t have real influence to the stock price. Then the result of the research showed that simultaneously, all of the variables that used in the research had a real influence to the stock price. As we could see that F test point is 21,466 and significance point is 0,000